Probing hepatic metabolism of [2-13C]dihydroxyacetone in vivo with 1H-decoupled hyperpolarized 13C-MR - Marco-Rius, I; Wright, AJ; Hu, D-E; Savic, D; Miller, JJ; Timm, KN; Tyler, D; Brindle, KM; Comment, A (Springer, 2020)
OBJECTIVES:To enhance detection of the products of hyperpolarized [2-13C]dihydroxyacetone metabolism for assessment of three metabolic pathways in the liver in vivo. Hyperpolarized [2-13C]DHAc emerged as a promising substrate to follow gluconeogenesis, glycolysis and the glycerol pathways. However, the use of [2-13C]DHAc in vivo has not taken off because (i) the chemical shift range of [2-13C]DHAc and its metabolic products span over 144 ppm, and (ii) 1H decoupling is required to increase spectral resolution and sensitivity. While these issues are trivial for high-field vertical-bore NMR spectrometers, horizontal-bore small-animal MR scanners are seldom equipped for such experiments. METHODS:Real-time hepatic metabolism of three fed mice was probed by 1H-decoupled 13C-MR following injection of hyperpolarized [2-13C]DHAc. The spectra of [2-13C]DHAc and its metabolic products were acquired in a 7 T small-animal MR scanner using three purpose-designed spectral-spatial radiofrequency pulses that excited a spatial bandwidth of 8 mm with varying spectral bandwidths and central frequencies (chemical shifts). RESULTS:The metabolic products detected in vivo include glycerol 3-phosphate, glycerol, phosphoenolpyruvate, lactate, alanine, glyceraldehyde 3-phosphate and glucose 6-phosphate. The metabolite-to-substrate ratios were comparable to those reported previously in perfused liver. DISCUSSION:Three metabolic pathways can be probed simultaneously in the mouse liver in vivo, in real time,  using hyperpolarized DHAc.